Methodological Aspects of Teaching Academic Writing at the University - Jalolovna, Mirzaeva Nasibakhan (Miasto Przyszłości, 2023)
This article discusses the study of modern quality standards of higher education in relation to the teaching of a foreign language in the aspect of academic writing for students.